2020
DOI: 10.14338/ijpt-20-00006.1
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Verification CT-QA Scans in Patients Treated with IMPT for Head and Neck Cancers

Abstract: Purpose To understand how verification computed tomography-quality assurance (CT-QA) scans influenced clinical decision-making to replan patients with head and neck cancer and identify predictors for replanning to guide intensity-modulated proton therapy (IMPT) clinical practice. Patients and Methods We performed a quality-improvement study by prospectively collecting data on 160 consecutive patients with head and neck cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Even though tendencies of patterns for aeration changes were present for the group of patients with increasing air in the maxillary sinus in F1–5, anatomy-based evaluation was shown not to be a successful strategy, and there is a need for development of other adaptive strategies. The need for adaption and re-planning is highlighted by a study by Evans et al [21] , who evaluated the influence of regular quality assurance CT on the frequency of re-planning during a proton treatment course. They found the sinonasal disease site to be a significant predictor for re-planning, and concluded that the quality assurance strategy affected the adaptive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Even though tendencies of patterns for aeration changes were present for the group of patients with increasing air in the maxillary sinus in F1–5, anatomy-based evaluation was shown not to be a successful strategy, and there is a need for development of other adaptive strategies. The need for adaption and re-planning is highlighted by a study by Evans et al [21] , who evaluated the influence of regular quality assurance CT on the frequency of re-planning during a proton treatment course. They found the sinonasal disease site to be a significant predictor for re-planning, and concluded that the quality assurance strategy affected the adaptive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A relative biological effectiveness (RBE) of 1.1 for proton beams was used. The dosimetric goals and priorities for all plans in this study are summarised in Table 1 [4,[21][22][23]. Further details can be found in Appendix A.…”
Section: B Patient Datamentioning
confidence: 99%
“…7,8 In our clinic,we acquire a weekly QA CT for each head-and-neck (HN) cancer patient because tumor shrinkage is commonly observed. 9 The current practice is for the physicians to fuse the QA CT and the planning CT (pCT) using rigid/nonrigid registration to visualize any anatomical changes and then re-contour on the QA CT when large anatomical changes are observed. In these instances, new dose volume histograms (DVHs) are generated from the contoured CT QA images to quantify important dosimetric endpoints that guide the decision to continue with the current plan or replan.…”
Section: Introductionmentioning
confidence: 99%
“…Quality assurance (QA) CT scans can be regularly acquired in order to track the anatomical changes and assess the necessity of a replan to mitigate the aforementioned problems 7,8 . In our clinic, we acquire a weekly QA CT for each head‐and‐neck (HN) cancer patient because tumor shrinkage is commonly observed 9 . The current practice is for the physicians to fuse the QA CT and the planning CT (pCT) using rigid/nonrigid registration to visualize any anatomical changes and then re‐contour on the QA CT when large anatomical changes are observed.…”
Section: Introductionmentioning
confidence: 99%